Radiation Induced Cavernomas in the Treatment of Pediatric Medulloblastoma: Comparative Study Between Proton and Photon Radiation Therapy - Trybula, S. Joy; Youngblood, Mark W.; Kemeny, Hanna R.; Clark, Jeffrey R.; Karras, Constantine L.; Hartsell, William F.; Tomita, Tadanori (Frontiers in Oncology, 2021)
Radiation induced cavernomas among children with medulloblastoma are common following external beam radiation (XRT) treatment with either photon or proton beams. However, with the increased utilization of proton beam therapy over the last decade we sought to determine if there was any difference in the development or natural history of these cavernous malformations (CM) or CM-like lesions. We performed a retrospective analysis of 79 patients from 2003 to 2019 who had undergone resection of medulloblastoma and subsequent XRT (30 photon or 49 proton beam therapy). The average age of patients at radiation treatment was 8.7 years old. Average follow up for patients who received photon beam therapy was 105 months compared to 56.8 months for proton beam therapy. A total of 68 patients (86.1%) developed post-radiation CMs, including 26 photon and 42 proton patients (86.7% and 85.7% respectively). The time to cavernoma development was significantly different, with a mean of 40.2 months for photon patients and 18.2 months for proton patients (p = 1.98 x 10-4). Three patients, one who received photon and two who received proton beam radiation, required surgical resection of a cavernoma. Although CM or CM-like lesions are detected significantly earlier in patients after receiving proton beam therapy, there appears to be no significant difference between the two radiation therapy modalities in the development of significant CM requiring surgical resection or intervention other than continued follow up and surveillance.